Wacana Islam Geguritan Nurcaya Nursada (Tuan Semeru): Bentuk Moderasi Pemikiran dan Sinkretisme Islam-Hindu - Wiradnyana, I Made (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2023)
Tuan Semeru is a progressive figure from East Java who is better known as Danghyang Nirartha. The nickname Tuan Semeru is a gift from the Sasak people of Lombok which refers to the figure of a teacher who comes from the Mount Semeru area, East Java. Mr. Semeru himself is the figure who is strongly suspected of creating Geguritan Nurcaya Nursada. His background was a spiritualist and scholar of his time. This article intends to analyze the concepts of Geguritan Nurcaya Nursada in Islamic-Hindu syncretism. Qualitative method with literature review approach is used in this article. The results of the study reveal that the approach of Islamic values to the culture and beliefs of the local community by Sunan Kalijaga by using the wayang kulit media. Similar to Tuan Semeru, the Hindu and Buddhist values approach to Islam is also carried out with the aim of spreading dharma which in Islamic terms is equivalent in meaning to monotheism (God's provisions).